Experiences of goal planning in Australian community pharmacy settings for people experiencing mental illness: A qualitative study - Victoria Stewart; Sara S. McMillan; Jie Hu; Jack C. Collins; Sarira El‐Den; Claire O'Reilly; Amanda J. Wheeler (Wiley, 2023)
Abstract Background Person‐centred goal planning is increasingly being incorporated into healthcare interventions. People experiencing severe and persistent mental illnesses (SPMIs) have high levels of co‐occurring health conditions, reducing their life expectancy when compared with the general population. As medications are commonly used in the treatment of SPMIs, community pharmacists are well‐placed to support the health and wellbeing of this population. Objectives To examine pharmacists' and service users' experiences of goal planning as a component of a community pharmacy‐based health intervention for people experiencing SPMIs (PharMIbridge intervention). Methods This study utilised a qualitative exploratory approach with an interpretive description method. Semistructured interviews were undertaken with community pharmacists (n = 16) and service user participants (n = 26) who had participated in pharmacist support services for people experiencing SPMIs (PharMIbridge intervention). Results Four themes relating to goal planning were identified. First, goal planning provided purpose and motivation for participation in the intervention. Planning realistic goals was important but often challenging. Both pharmacists and service users highlighted the relational aspects of goal planning and how strong relationships supported positive behaviour change and outcomes. Finally, individualised and flexible approaches were important aspects of the intervention, ensuring goals were meaningful to service users. Conclusions The findings from this study identified positive outcomes from the inclusion of goal‐planning processes in a community pharmacy‐based health intervention. Further research regarding tools, strategies or training that could support future goal‐planning interventions in primary healthcare is needed. Patient or Public Contribution The PharMIbridge randomised controlled trial research team included lived experience members and was overseen by an expert panel that included members with a lived experience of mental illness and representatives from key organisations. The training provided to pharmacists was co‐designed and co‐delivered by the researchers and lived experience representatives, and pharmacists were supported by lived experience mentors. Service user participants were invited to participate in the interviews through a number of pathways (e.g., at the completion of the intervention, flyers). Those interested were provided with the full study participant information and provided with a $30 gift voucher at the conclusion of the interview.